Money Politic VS Political Marketing: Studi Kasus: Pemilihan Anggota Legislatif DPRD Kabupaten Pringsewu Periode 2019-2024 - Utami, Bernadhita Herindri Samodera; Herinanto, Dwi; Gumanti, Miswan; Purwanto, Bambang (Jurnal Bina Praja, 2020)
The meaning of "sovereignty is in the hands of people" namely that people have sovereignty, responsibilities, rights, and participatory political obligations to democratically elect a leader who can form a government to take care of and serve all levels of society, as well as electing people's representatives to oversee the running of the government. However, the phenomena that occur are democratic parties, presidential elections, elections, and legislative elections are always colored by systemic money politics. This research using the quantitative method. Primary data were obtained by survey. The writer then describes the public opinion about the Pringsewu District Legislative Council Members' election for the 2019-2024 period on political marketing and money politics. The results showed that 40.37% of voters gave support to legislative candidates for reasons of money.